EFFECT OF ARBUSCULAR MYCORRHIZAL (AM) INOCULATION ON UPLAND RICE ROOT SYSTEM - TOPPO, NEHA NANCY; A.K SRIVASTAVA; MAITI, DIPANKAR (The Bioscan, 2013)
ABSTRACT This paper provides a brief assessment of the effect of AM (arbuscular mycorrhizal) inoculation on certain root morphological characters (root length, root diameter, root surface area, root volume, root length density) and branching pattern (fractal dimension) of upland rice (Oryza sativa L.) an important food grain crop. The uplands in India being rainfed is drought prone and crop productivity is severely crippled due to major constraint of inefficient phosphorus (P) acquisition. The effects of AM fungi (AMF) on enhancing rice plant growth, P uptake and yield are well-acknowledged. The present investigation will aid in generating information on influence of AMF association on rice root growth which would provide further clues for possible exploitation of AMF activities in favor of rice crop. For this, three upland varieties, Sathi 34-36 (highly AM-responsive), Jonga (AM non-responsive) and Vandana (moderately AM-responsive) were selected. AM-responsiveness of these three varieties was measured as a change in total dry matter production as a result of AM-symbiosis (on inoculation with AM fungi). P uptake at 40 DAE (days of emergence) under un-inoculated low P conditions for the three rice varieties was also evaluated with Sathi 34-36 having the highest tissue P content. Root morphological attributes like root length density, total root length, root diameter, root volume and root surface area were increased on AMF inoculation in both responsive (Sathi 34-36) and non-responsive (Jonga) variety with higher magnitude only in non-responsive variety (Jonga). Thus, AM-responsive variety (Sathi 34-36) having higher P-demand (due to increased P-uptake) was more dependent on mycorrhizal pathway for P acquisition than non-responsive (Jonga) variety. Between responsive varieties, Sathi 34-36 along with its inherent better P demand compared to Vandana was altered significantly in root morphology suggesting that varieties with high P uptake ability under low P conditions would be more responsive to AM inoculation and thus would be more likely to undergo root morphological changes.